Selective Conversion of CO2 and Switchable Alcohols into Linear or Cyclic Carbonates via Versatile Zinc Catalysis - Song, Qing-Wen; Zhao, Qing-Ning; Li, Jing-Yuan; Zhang, Kan; Liu, Ping (Synthesis, 2019)
It is promising and challenging to achieve the effective construction of carbonates using CO2 and a non-noble metal catalyst. Herein, selective catalytic conversion of CO2 and switchable alcohol candidates to produce linear or cyclic carbonates and α-hydroxy ketones via effective zinc catalyst was developed. A series of primary alcohols and cyclohexanol, 1,2-diols, and water can serve as nucleophiles to give alkyl or aryl 2-substituted-3-oxobutan-2-yl carbonates, substituted 1,3-dioxolan-2-ones, 3-substituted 3-hydroxybutan-2-ones, respectively with excellent selectivity and high yields.
Keywords: carbon dioxide utilization; carbonates; zinc catalysis; multicomponent reaction; synthetic methods